Seasonal variation in haematological and biochemical reference values for healthy young children in The Gambia. Issue 1 (December 2016) - Okebe, Joseph; Mwesigwa, Julia; Agbla, Schadrac; Sanya-Isijola, Frank; Abubakar, Ismaela; D'Alessandro, Umberto; Jaye, Assan; Bojang, Kalifa
Abstract Background Haematological and biochemistry reference values for children are important for interpreting clinical and research results however, differences in demography and environment poses a challenge when comparing results. The study defines reference intervals for haematological and biochemistry parameters and examines the effect of seasonality in malaria transmission. Methods Blood samples collected from clinically healthy children, aged 12–59 months, in two surveys during the dry and wet season in the Upper River region of The Gambia were processed and the data analysed to generate reference intervals based on the 2.5th and 97.5th percentiles of the data. Results Analysis was based on data from 1141 children with median age of 32 months. The mean values for the total white cell count and differentials; lymphocyte, monocyte and neutrophil decreased with increasing age, were lower in males and higher in the wet season survey. However, platelet values declined with age (p < 0.0001). There was no evidence of effect of gender on mean values of AST, ALT, lymphocytes, monocytes, platelets and haemoglobin. Conclusion Mean estimates for haematological and biochemistry reference intervals are affected by age and seasonality in the first five years of life. This consistency is important for harmonisation of reference values for clinical care and interpretation of trial results.